Socio-economic impacts of tourism businesses in Okahandja: A case study of Nau-Aib (Journal for Studies in Humanities and Social Sciences, 2016)
Tourism is one of the biggest and fastest growing industries in the world and its development is a major concern for developing countries. Its growth carries with it both negative and positive impacts on the local economy and the people of those countries where tourism is a significant sector. The purpose of this paper is to analyse the socio-economic influence of tourism businesses on the com-munity of Nau-Aib in Okahandja, using Edward’s (2005) socio-economic indicators. The results of a socio-economic impact assessment can inform a community about the wide scope of tourism impacts on their social and economic wellbeing. The study area of this research was Nau-Aib, one of the big-gest locations in Okahandja. Face to face interviews were conducted with 40 respondents residing in Nau-Aib. Tourism businesses, such as the arts and crafts market in Okahandja, and hospitality busi-nesses situated in the vicinity of Nau-Aib, were the focus for this study, as these businesses often en-gage in commercial activities that carry with them socio-economic impacts for adjacent communi-ties. Okahandja’s tourism sector generally employs local people. However, these jobs are mostly me-nial entry level jobs that pay employees modest salaries. Through its multiplier effect, the sector also encourages business growth in Nau-Aib, mainly in the informal sector, and induces improvements in public service utilities and infrastructural development at tourism significant areas to facilitate tour-ism activities.